THE ATTRACTIVENESS OF SHOPEE ADVERTISEN ADVERTISEMENTT TO BUYER INTEREST - Shahnaz Sabahunnur Kautsar; Azzahra Aisya Rahmi; Wahyunengsih Wahyunengsih (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2022)
The purpose of this research is to find out the special buyer's interest in journalism students in reading the submitted advertisements.This research uses qualitative research to facilitate data collection to be analyzed. This research into the attractiveness of shopee advertising will result in detailed research and knowledge based on an attempt to build a view that is formed from a complex big picture. From the results of the study and the results of the discussion of this study, it can be concluded that the 2022 journalism students agree with the attractiveness of shopee advertisements attracting buying interest. Because the ads that are delivered are clear, creative, and have audio that can make people who watch the ad that runs until it runs out. From the ad impressions that were delivered, they received a positive response, making the audience watch until the end.